The population of rice leaf folder (Cnaphalocrosis medinalis) in paddy field at Melaka / Nursyuairah Abu Hasan and Amira Hamid - Abu Hasan, Nursyuairah; Hamid, Amira (Faculty of Plantation and Agrotechnology, 2018)
Leaf folder (Cnapalocrosis medinalis) is one of the major insect pests that affect the rice production in Melaka. Infestation of leaf folder will disturb the paddy growth because of the larvae will eat the outer surface of leaves that contain chlorophyll thus it disturbs the photosynthesis process. This study was conducted purposely to know the population of leaf folder in paddy fields and the difference of abundance of leaf folder in paddy field between the three areas involved. The data of leaf folder was taken from Biosecurity unit of Pulau Gadong. The data collected consists of areas affected by leaf folder for 3 years starting from 2016 until 2018. The study areas that involved were Melaka Tengah, Alor Gajah and Jasin. The result of the study showed that Alor Gajah has the highest percentage of leaf folder infestation. It happened due to the high usage of fertilizer and insecticide and also rainy and cloudy weather. Melaka Tengah showed the lowest percentage of areas that were affected by leaves folder. However, this study showed that leaf folder was not the major insect that attacks paddy field in Melaka because the total percentage of damage is lower than economic injury level.